PENGARUH SISTEM PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KEPUASAN DAN MOTIVASI KERJA APARATUR SIPIL NEGARA (ASN) DI DINAS PARIWISATA PEMUDA DAN OLAHRAGA KOTA BIMA - Saiful Akbar; Hermanto Hermanto; Agus Susanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to reveal the effect of the system of providing additional employee income (TPP) on satisfaction and work motivation of State Civil Apparatus (ASN) at the Department of Tourism, Youth and Sports, Bima City. The population and sample in this study amounted to 32 people. The research instrument used questionnaires, and interviews. Then the data were analyzed by multiple linear regression. The results of the research are that: (1) There is a direct significant effect of the Employee Income Supplemental Provision System on State Civil Apparatus Employees; (2) there is a direct significant effect of job satisfaction on State Civil Apparatus Employees; (3) there is a direct significant effect of the Employee Income Supplement System on Job Satisfaction and Motivation in a stimulant manner; (4) it is known that the direct effect given by job satisfaction on Z (Bima City Youth and Sports Tourism Office) is 0.146. Meanwhile, the indirect effect of job satisfaction through Y (State Civil Apparatus) on Z (Bima City Youth and Sports Tourism Office) is 0.247. So the total effect given by job satisfaction on Z (Department of Tourism, Youth and Sports City of Bima) is a direct effect plus an indirect effect, namely: 0.146 +0.247 = 0.393. With the additional income of employees in the form of facsimile so that it affects job satisfaction and motivation of the State Civil Apparatus (ASN). Additional Employee Income (Incentives) in the form of facsimile will motivate the performance of the State Civil Apparatus at the Bima City Tourism Office.